Melatonin Prevents Chronic Kidney Disease-Induced Hypertension in Young Rat Treated with Adenine: Implications of Gut Microbiota-Derived Metabolites - Chien-Ning Hsu; Hung-Wei Yang; Chih-Yao Hou; Guo-Ping; Sufan Lin; You-Lin Tain (MDPI AG, 2021)
Melatonin, a signaling hormone with pleiotropic biofunctions, has shown health benefits. Trimethylamine-N-oxide (TMAO) and asymmetric dimethylarginine (ADMA) are uremic toxins involved in the development of hypertension. TMAO originates from trimethylamine (TMA), a gut microbial product. ADMA is an endogenous nitric oxide (NO) synthase inhibitor. We examined whether melatonin therapy could prevent hypertension and kidney disease by mediating gut microbiota-derived metabolites and the NO pathway using an adenine-induced chronic kidney disease (CKD) young rat model. Six-week-old young Sprague Dawley rats of both sexes were fed a regular diet (C group), a diet supplemented with 0.5% adenine (CKD group), or adenine plus 0.01% melatonin in their drinking water (CKD + M group) for three weeks (N = 8/group). Adenine-fed rats developed renal dysfunction, hypertension, renal hypertrophy and increased uremic toxin levels of TMAO and ADMA. Melatonin therapy prevented hypertension in both sexes and attenuated kidney injury in males. Melatonin reversed the changes to the plasma TMAO-to-TMA ratio induced by CKD in both sexes. Besides, the protective effects of melatonin were associated with restoration of gut microbiota alterations, including increased α-diversity, and enhancement of the abundance of the phylum Proteobacteria and the genus Roseburia in male rats. Melatonin therapy also partially prevented the increases in ADMA in male CKD rats. Melatonin sex-specifically protected young rats against hypertension and kidney injury induced by CKD. The results of this study contribute toward a greater understanding of the interaction between melatonin, gut microbiota-derived metabolites, and the NO pathway that is behind CKD, which will help to prevent CKD-related disorders in children.